Trilingual modality: Towards an analysis of mood and modality in Aymara, Quechua and Castellano Andino as a joint systematic concept - Dankel, Philipp (2022)
This contribution examines how indigenous minority languages impact majority European ones, by considering the case of Quechua and Aymara, on the one side, and Castellano Andino (CA) on the other. We extend particular focus to how Aymara and Quechua have impacted CA's grammatical(ized) modality. We show that regional varieties of CA reflect Aymara and Quechua mood, even in the speech those who do not speak either indigenous language by illustrating the emerging strategies used to express the modal values in Aymara and Quechua grammar on different structural levels. We also elaborate on how contact induced change arises from multiple impulses.